Comparative state feminism - Mazur, Amy; McBride, Dorothy E. (Sage Publications, 1995)
The cross-national trend in post-industrial societies of establishing state structures assigned to improve the status of women is studied in this book. The existence of a phenomenon called `state feminism' has begun to be a focus of research in the past few years, although the phenomenon itself dates from the 1960s, thus there is a clear need for a comparative analysis. With contributions from renowned scholars, the book: describes and classifies the range and diversity of state structures charged with improving the status of women in post-industrial societies; analyzes their effect on the status of women on achieving feminist goals; and explains the variations among post-industrial societies in the establishment, elaboration and effectiveness of such state structures.